2016
DOI: 10.1016/j.jped.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of eating frequency with anthropometric indices and blood pressure in children and adolescents: the CASPIAN-IV Study

Abstract: Higher EF was associated with lower mean values of anthropometric and BP measures, as well as with lower prevalence of generalized and abdominal obesity in children and adolescents. Longitudinal studies are needed to assess the long-term effects of EF on body composition in the pediatric age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
20
0
3
Order By: Relevance
“…There is another argument that C&S introduces yet another eating occasion for primary school children and number of eating occasions has been positively associated with obesity in some studies among adults 14 and children, 15 although findings to date are mixed and the relationship equivocal. [16][17][18][19] Nonetheless, qualitative data from this study showed that there was a positive impact in terms of children bringing fewer packaged and processed fruit products to school, at least for the C&S breaks. This observation together with the numerous other benefits observed in this study and in other evaluations, 5,13,20,21 such as sustained focus in class and increased child awareness of and preferences for fruit and vegetables, indicates that the benefits of the C&S program most likely outweigh any potential negatives, providing that equitable reach can be achieved.…”
Section: Box 1 Example Quotes From the Post-intervention Key School mentioning
confidence: 66%
“…There is another argument that C&S introduces yet another eating occasion for primary school children and number of eating occasions has been positively associated with obesity in some studies among adults 14 and children, 15 although findings to date are mixed and the relationship equivocal. [16][17][18][19] Nonetheless, qualitative data from this study showed that there was a positive impact in terms of children bringing fewer packaged and processed fruit products to school, at least for the C&S breaks. This observation together with the numerous other benefits observed in this study and in other evaluations, 5,13,20,21 such as sustained focus in class and increased child awareness of and preferences for fruit and vegetables, indicates that the benefits of the C&S program most likely outweigh any potential negatives, providing that equitable reach can be achieved.…”
Section: Box 1 Example Quotes From the Post-intervention Key School mentioning
confidence: 66%
“…Similarly, Gómez--Martinez et al [19] observed that adolescents in Spain who ate breakfast regularly had lower means of waist circumference and skinfold measurements. The results of international studies have indicated an inverse association between the number of daily meals and the risk of excess abdominal adiposity [9,20].…”
Section: The Association Between Meal Consumption Habits and Body Commentioning
confidence: 99%
“…However, an aspect that has not yet been explored in the literature is the possible relationship between the presence of parents at meals and the nutritional status of adolescents. The influence of socioeconomic factors on the association between eating habits and adiposity indicators is also being newly considered in studies in Brazil [9,13,17] and in other countries [15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A existência de uma transição alimentar da infância para a adolescência, caracterizada por mudanças relevantes que podem impactar na saúde dos indivíduos, como a diminuição da frequência de refeições, incremento no tamanho das porções, aumento do consumo de alimentos com alta densidade energética e pobre em nutrientes, ingestão de alimentos fora de casa, refeições realizadas na ausência da família, entre outras, têm se destacado por representarem comportamentos de risco para o excesso de peso e outras complicações (ALBAR et al, 2014;GARCIA-CONTINENTE et al, 2015;HAGHIGHATDOOST et al, 2017). (RITCHIE, 2012;JAASKELAINEN et al, 2013, HOUSE et al, 2015KELISHADI et al, 2016). -NETO et al, 2016).…”
Section: Discussionunclassified
“…Estudos brasileiros populacionais demonstram significativa variação na prevalência de dislipidemia entre crianças e adolescentes, que pode ser observada de 10 até 47%, dependendo da região e critério utilizado (GIULIANO et al, 2005;DE FRANCA;ALVES, 2006;FARIA-NETO et al, 2016). (FRANKO et al, 2008;MOTA et al, 2008;KOLETZKO;TOSCHKE, 2010;JÄÄSKELÄINEN et al, 2013;HOUSE et al, 2015;KELISHADI et al, 2016;SILVA et al, 2017 Os adolescentes que realizavam um maior número de refeições diárias, ou seja, seis refeições ou mais, apresentaram associação inversa para obesidade abdominal, de acordo com a razão cintura/estatura, comparado àqueles que realizavam três ou menos (OR 0,33 -IC 95% 0,13; 0,81). Além disso, encontrou-se um p de tendência significativo (p=0,04), indicando menor chance de obesidade abdominal conforme o aumento da frequência de refeições.…”
Section: Dislipidemiaunclassified